Marking method for dung beetles (Coleoptera: Scarabaeinae) and its implementation in Colombian Andes - Martínez-Quintero, Bedir G.; Cultid-Medina, Carlos A.; Rudas-Grajales, Juan C. (Instituto de Ecología, A.C., 2013)
We describe a new inexpensive and simple method for marking large dung beetles (>10 mm), which consists in tattooing a consecutive number on their elytra or pronotum with a Mototool. The recapture rate (18.5% of 1886 marked individuals) throughout five months shows high durability of the mark without affecting the integrity of the individual.